PhotoBioLib: A Modelica library for modeling and simulation of large-scale photobioreactors. (4th March 2017) - Perez-Castro, A.; Sanchez-Moreno, J.; Castilla, M.
Abstract : Highlights: A Modelica library for the modeling and simulation of photobioreactors is presented. The modeling equations are based on first principles. The library is easy to use, fast and highly configurable. The library has been validated with real data. Its easy to interconnect other models or libraries to create more complex systems. Abstract: This paper presents PhotoBioLib, a library developed in Modelica language for modeling and simulation of industrial tubular photobioreactors without necessity of a previous knowledge of programming neither the involved dynamics. Therefore, it provides models very similar to the real ones, with a high configuration potential, interconnection possibilities with other libraries and a high simulation speed. The library has been validated with real data.